Effect of banana peel flour incorporation (Musa acuminata) on physicochemical and sensory profile of chicken sausage - Hana Mohd Zaini; Mohd. Dona Sintang; Suryani Saallah; Noorakmar Ab. Wahab; Jumardi Roslan; Wolyna Pindi (UniSE Press, 2021)
The study was conducted to determine the physicochemical and sensory properties of chicken sausages added with banana peel flour (BPF) in different percentages of BPF (2%, 4% and 6%). The use of BPF in sausage formulations did have a significant effect (P < 0.05) on the proximate compositions, dietary fibre and mineral content of the sausages. By increasing the proportion of BPF in the sausage 4 to 6%, the hardness was increased by 31% and 54% respectively (P < 0.05). The darker sausage was obtained as more BPF added in the formulation. The sensory evaluation showed that the chicken sausage with a concentration of 2% had the highest overall acceptability. In comparison, a sausage containing 6% was found to be the least acceptable compared to the control sample. The declining sensory acceptability of the sausages with 6% BPF was related to its hard texture and dark colour.